Impact of the use of local fidaxomicin treatment algorithms for managing Clostridium difficile infection in hospitalized patients in southeastern United States - Jonathan C. Cho; Sandy J. Estrada; Jamie J. Kisgen; Angelina Davis; Laura Puzniak (BMC, 2018)
Abstract Background Clostridium difficile-associated diarrhea (CDAD) is a major public health threat that results in increased length of stay, hospital readmissions, deaths, and economic burden. CDAD treatment is often guided by severity of disease. Although various tools exist to determine CDAD severity, real-world data evaluating the use of such tools in treatment algorithms are sparse. Methods A local CDAD treatment pathway was developed independently to guide fidaxomicin prescribing at wellStar Health System (WellStar) and at Lee Health (LH) and Sarasota Memorial Hospital (SMH). Each algorithm was designed locally by the stewardship pharmacist and was utilized to identify patients at high risk for C. difficile recurrence. Patient and clinical data was retrospectively gathered to evaluate the utility and outcomes of the treatment pathway. Results There were 262 patients that received fidaxomicin at these three hospitals during the study time period. Only 30% at WellStar and 20% at LH or SMH met the study criteria and adhered to the pathway requirements. After completion of fidaxomicin, 30-day recurrence rates at WellStar was 0 and at LH and SMH 7%. Clinical cure rates were 83% in WellStar and 93% in LH and SMH. Conclusions The results from these two pathways show positive outcomes for the use of fidaxomicin in patients at high risk for CDAD recurrence. This data supports the potential utility of fidaxomicin against CDAD.